Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To show that the polynomial function [tex]\( f(x) = x^4 - 6x^3 - 30x^2 + 48x + 136 \)[/tex] has a real zero between the numbers [tex]\( -4 \)[/tex] and [tex]\( -3 \)[/tex], we will use the Intermediate Value Theorem. The Intermediate Value Theorem states that if a function [tex]\( f \)[/tex] is continuous on a closed interval [tex]\([a, b]\)[/tex] and if [tex]\( f(a) \)[/tex] and [tex]\( f(b) \)[/tex] have opposite signs, then there is at least one [tex]\( c \)[/tex] in the interval [tex]\((a, b)\)[/tex] such that [tex]\( f(c) = 0 \)[/tex].
First, let's calculate the value of the polynomial at [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = (-4)^4 - 6(-4)^3 - 30(-4)^2 + 48(-4) + 136 \][/tex]
Simplifying this step-by-step:
[tex]\[ (-4)^4 = 256 \][/tex]
[tex]\[ -6(-4)^3 = -6(-64) = 384 \][/tex]
[tex]\[ -30(-4)^2 = -30(16) = -480 \][/tex]
[tex]\[ 48(-4) = -192 \][/tex]
Adding these results together:
[tex]\[ f(-4) = 256 + 384 - 480 - 192 + 136 = 104 \][/tex]
So, [tex]\( f(-4) = 104 \)[/tex].
Next, let's calculate the value of the polynomial at [tex]\( x = -3 \)[/tex]:
[tex]\[ f(-3) = (-3)^4 - 6(-3)^3 - 30(-3)^2 + 48(-3) + 136 \][/tex]
Simplifying this step-by-step:
[tex]\[ (-3)^4 = 81 \][/tex]
[tex]\[ -6(-3)^3 = -6(-27) = 162 \][/tex]
[tex]\[ -30(-3)^2 = -30(9) = -270 \][/tex]
[tex]\[ 48(-3) = -144 \][/tex]
Adding these results together:
[tex]\[ f(-3) = 81 + 162 - 270 - 144 + 136 = -35 \][/tex]
So, [tex]\( f(-3) = -35 \)[/tex].
Since [tex]\( f(-4) = 104 \)[/tex] is positive and [tex]\( f(-3) = -35 \)[/tex] is negative, the signs change between [tex]\( f(-4) \)[/tex] and [tex]\( f(-3) \)[/tex]. According to the Intermediate Value Theorem, this indicates that there is at least one zero of the polynomial between [tex]\( -4 \)[/tex] and [tex]\( -3 \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{\text{B. A zero of the polynomial lies between -4 and -3.}} \][/tex]
First, let's calculate the value of the polynomial at [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = (-4)^4 - 6(-4)^3 - 30(-4)^2 + 48(-4) + 136 \][/tex]
Simplifying this step-by-step:
[tex]\[ (-4)^4 = 256 \][/tex]
[tex]\[ -6(-4)^3 = -6(-64) = 384 \][/tex]
[tex]\[ -30(-4)^2 = -30(16) = -480 \][/tex]
[tex]\[ 48(-4) = -192 \][/tex]
Adding these results together:
[tex]\[ f(-4) = 256 + 384 - 480 - 192 + 136 = 104 \][/tex]
So, [tex]\( f(-4) = 104 \)[/tex].
Next, let's calculate the value of the polynomial at [tex]\( x = -3 \)[/tex]:
[tex]\[ f(-3) = (-3)^4 - 6(-3)^3 - 30(-3)^2 + 48(-3) + 136 \][/tex]
Simplifying this step-by-step:
[tex]\[ (-3)^4 = 81 \][/tex]
[tex]\[ -6(-3)^3 = -6(-27) = 162 \][/tex]
[tex]\[ -30(-3)^2 = -30(9) = -270 \][/tex]
[tex]\[ 48(-3) = -144 \][/tex]
Adding these results together:
[tex]\[ f(-3) = 81 + 162 - 270 - 144 + 136 = -35 \][/tex]
So, [tex]\( f(-3) = -35 \)[/tex].
Since [tex]\( f(-4) = 104 \)[/tex] is positive and [tex]\( f(-3) = -35 \)[/tex] is negative, the signs change between [tex]\( f(-4) \)[/tex] and [tex]\( f(-3) \)[/tex]. According to the Intermediate Value Theorem, this indicates that there is at least one zero of the polynomial between [tex]\( -4 \)[/tex] and [tex]\( -3 \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{\text{B. A zero of the polynomial lies between -4 and -3.}} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.